Towards a SMART broadband Caribbean Community : editorial (2013)
Presents a report on the CANTO 29th Annual Conference and Trade Exhibition held in Aruba from 14th to 19th July 2013. Shares the perspectives of the government ministers from ten Caribbean countries on broadband development in their respective countries.
Keywords: TELECOMMUNICATIONS NETWORKS